Internet of Things (IoT) Based Radiation Exposure Monitoring System Data Collection, Analysis, and Alerting in Occupational En-vironments - Evita Ayu Suryaningtyas; Kusworo Adi; Dartini Dartini; Gatot Murti Wibowo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Examinations in radiology installations have increased annually, resulting in a higher risk of radiation hazards to staff, particularly in interventional, conventional X-ray, and CT-Scan environments. Furthermore, not all hospitals are equipped with radiation survey meter monitoring devices. Therefore, an innovative radiation exposure monitoring system based on the Internet of Things (IoT) was developed. This study aims to: (1) develop an IoT-based radiation exposure monitoring system, (2) evaluate the device’s performance, and (3) assess the effectiveness of the system. The research method used was research and development (R&D), which included preliminary information gathering, product planning and development, expert validation, device performance testing, effectiveness testing, and final outcomes. This system was developed for real-time radiation dose monitoring. The product development involved a Geiger-Muller M4011, an ESP32 microcontroller, and a Node-Red web application. Performance testing of the IoT-based radiation exposure monitoring device and a standard survey meter in CT-Scan and conventional X-ray rooms used the T-Test and Mann-Whitney tests. The results showed p-values > 0.05, indicating no significant difference between the two devices. Effectiveness testing through pre-test and post-test questionnaires demonstrated improved usability—namely flexibility, operability, learnability, and understandability—with an N-Gain value of 78.95%, indicating effectiveness. In conclusion, the IoT-based radiation exposure monitoring system proved effective and feasible for real-time radiation dose monitoring in radiology installations, offering advantages in IoT-based data integration, ease of access, and structured data recording. In addition to performance testing, the system was evaluated in terms of its integration with hospital infrastructure. It was designed to provide real-time radiation dose monitoring, automatically updating the dose data and sending alerts when safe exposure levels are exceeded. The system also enables remote monitoring, making it easier for radiology departments to oversee radiation safety without the need for direct physical checks.